Features of effective staff training programmes within school-based interventions targeting student activity behaviour: a systematic review and meta-analysis - Mairead Ryan; Olivia Alliott; Erika Ikeda; Jian'an Luan; Riikka Hofmann; Esther van Sluijs (BMC, 2022)
Abstract Background Evaluations of school-based activity behaviour interventions suggest limited effectiveness on students' device-measured outcomes. Teacher-led implementation is common but the training provided is poorly understood and may affect implementation and student outcomes. We systematically reviewed staff training delivered within interventions and explored if specific features are associated with intervention fidelity and student activity behaviour outcomes. Methods We searched seven databases (January 2015-May 2020) for randomised controlled trials of teacher-led school-based activity behaviour interventions reporting on teacher fidelity and/or students' device-measured activity behaviour. Pilot, feasibility and small-scale trials were excluded. Study authors were contacted if staff training was not described using all items from the Template for Intervention Description and Replication reporting guideline. Training programmes were coded using the Behaviour Change Technique (BCT) Taxonomy v1. The Effective Public Health Practice Project tool was used for quality assessment. Promise ratios were used to explore associations between BCTs and fidelity outcomes (e.g. % of intended sessions delivered). Differences between fidelity outcomes and other training features were explored using chi-square and Wilcoxon rank-sum tests. Random-effects meta-regressions were performed to explore associations between training features and changes in students' activity behaviour. Results We identified 68 articles reporting on 53 eligible training programmes and found evidence that 37 unique teacher-targeted BCTs have been used (mean per programme = 5.1 BCTs; standard deviation = 3.2). The only frequently identified BCTs were 'Instruction on how to perform the behaviour' (identified in 98.1% of programmes) and 'Social support (unspecified)' (50.9%). We found moderate/high fidelity studies were significantly more likely to include shorter (≤6 months) and theory-informed programmes than low fidelity studies, and 19 BCTs were independently associated with moderate/high fidelity outcomes. Programmes that used more BCTs (estimated increase per additional BCT, d: 0.18; 95% CI: 0.05, 0.31) and BCTs 'Action planning' (1.40; 0.70, 2.10) and 'Feedback on the behaviour' (1.19; 0.36, 2.02) were independently associated with positive physical activity outcomes (N = 15). No training features associated with sedentary behaviour were identified (N = 11). Conclusions Few evidence-based BCTs have been used to promote sustained behaviour change amongst teachers in school-based activity behaviour interventions. Our findings provide insights into why interventions may be failing to effect student outcomes. Trial registration PROSPERO registration number: CRD42020180624